2018
DOI: 10.1103/physrevd.98.056009
|View full text |Cite
|
Sign up to set email alerts
|

Diffraction at a time grating in electron-positron pair creation from the vacuum

Abstract: The Sauter-Schwinger process of electron-positron pair creation from vacuum, driven by a sequence of time-dependent electric-field pulses, is studied in the framework of quantum-field theoretical approach. As demonstrated by our numerical results, the probability distributions of produced pairs exhibit intra-and inter-pulse interference structures. We show that such structures can be observed beyond the regime of applicability of the WKB theory, which was the focus of earlier investigations. Going beyond these… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 36 publications
3
26
0
Order By: Relevance
“…3. This fine structure in momentum spectrum for large ∆ could be related to the time-energy uncertainty principle: large ∆, being the longer characteristic time for energy change of the system, corresponds to more frequent changes in energy(momentum) of the system [35].…”
Section: B Two Symmetric Sauter Pulsesmentioning
confidence: 99%
See 1 more Smart Citation
“…3. This fine structure in momentum spectrum for large ∆ could be related to the time-energy uncertainty principle: large ∆, being the longer characteristic time for energy change of the system, corresponds to more frequent changes in energy(momentum) of the system [35].…”
Section: B Two Symmetric Sauter Pulsesmentioning
confidence: 99%
“…One of the profound features of Schwinger pair production is the interference effect shown to be present in the momentum distribution of created particles in temporal pulses with subcycle structure or multiple pulses of alternating signs [11,34,35]. Such interference effects can be explained semiclassically in terms of interference between pairs of turning points in the complex plane [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the production process is highly sensitive to the precise form of the applied field [10,11,12,13,14,15,16] and systematic analyses to find optimal pulse shapes for pair production were performed [17,18,19,20]. In trains of electric pulses, coherent enhancements due to multiple-slit interferences in the time domain were found [21,22,23,24,25]. Particularly strong amplification of pair production is expected to occur in bichromatic fields, consisting of weak high-frequency and strong low-frequency components [26,27,28,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…is satisfied [21]. In the presence of the time-dependent electric field, the fermionic field operator can be decomposed into eigenmodes which are labeled by the linear momentum p. In the following, we will relate to its longitudinal p and transverse p ⊥ components being defined with respect to the electric field direction,…”
Section: Theoretical Formulationmentioning
confidence: 99%
“…Another disadvantage is that the process is very weak. Hence, various proposals have been put forward aiming at enhancing the signal of electron-positron pairs [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Thus, raising the question of optimal control of the process [22,23].…”
Section: Introductionmentioning
confidence: 99%